Immune instructive materials for dendritic cell modulation - Kämmerling, Lisa (2021)
With most cytokine-based immunotherapies not fulfilling the promise of efficacy seen in pre-clinical experiments and often being associated with severe dose-limiting toxicities, biomaterial-based immunotherapies have emerged as powerful tools in different clinical settings including cancer vaccines and inflammatory diseases. Dendritic cells (DCs) play a central role in regulating adaptive immune responses making them ideal targets for immune modulation. To study the effect of polymer chemistry on DCs a screening of a polymer library constituted of acrylates, methacrylates and acrylamides was performed. Both stimulatory and regulatory polymers that instructed or inhibited DC activation respectively were identified. Stimulatory polymers instructed an immunogenic DC phenotype in the absence of any other exogenous stimuli leading to improved interaction with T cells, while regulatory polymers rendered DCs less responsive to TLR-4 stimulation and induced limited T cell proliferation. To elucidate the mechanisms of the observed polymer induced modulation in behaviour and phenotype of DCs, the coating stiffness and thickness of adsorbed proteins from serum supplemented culture medium on scaled up polymers were investigated. Two stimulatory hit polymers were additionally tested in an in vitro breast cancer-based tumour assay, showing the successful induction of tumour specific cytotoxic T lymphocytes that killed breast cancer cells efficiently. To investigate molecular changes of DCs cultured on stimulatory polymers, microarray analysis was performed to detect the expression levels of more than 21,000 genes. A short study into topography-induced DC modulations revealed that certain topographies render DC less responsive to LPS stimulus as well as slowed down DC motility, presenting a clear relationship between feature spacing and speed. In summary, findings from this study demonstrate the ability of polymer surfaces to modulate DC phenotype and function.